What is the impact of structural changes in society on diabetes self-management and trajectories of HbA1c? A cohort study before, during and after the COVID-19 pandemic in people with diabetes treated at outpatient clinics - Martin Gillies Banke Rasmussen; Emilie Just-Østergaard; Jacob Volmer Stidsen; Ingrid Willaing; Grete Skøtt Pedersen (PLoS ONE, 2025)
Background The impact of COVID-19-related changes in diabetes self-management and trajectories of HbA1c throughout COVID-19 is not fully understood. Here, we describe HbA1c trajectories, changes in diabetes self-management and their association before, during and after the COVID-19 pandemic (2019–2022). Methods During the spring of 2021, we invited 13,641 outpatients from diabetes clinics in the Region of Southern Denmark to complete a questionnaire regarding changes in diabetes self-management during COVID-19. We linked the questionnaire and registry HbA1c data from before, during and after the COVID-19 pandemic and conducted multivariable adjusted linear mixed-effect regression to assess the association between changes in diabetes self-management and HbA1c. Results 5,581 (40.9%) people responded to the questionnaire (median age: 65 years, males: 59.7%). HbA1c decreased in people with type 2-diabetes and was unchanged for people with type 1-diabetes (interaction: p < 0.001). The majority of people reported unchanged diet (65–71%) and usual medication taking (89–90%). No changes in physical activity were reported by 43%, while 42% reported decreased physical activity. HbA1c trajectories did not differ according to change in physical activity and change in diet intake, while taking medication more regularly was associated with a decrease in HbA1c, from approximately 65/66 mmol/mol (8.1/8.2%) to 60/61 mmol/mol (7.6/7.7%) in both diabetes types. Conclusions During COVID-19, HbA1c trajectories differed between diabetes types. Most of the sample maintained usual diabetes self-management, although some decreased physical activity levels. Improved medication taking was associated with decreased HbA1c. This information is crucial for health professionals, in order to provide support aimed at reducing HbA1c.